Strategi Komunikasi Tvri Sulawesi Selatan Dalam Meningkatkan Eksistensi Sebagai Lembaga Penyiaran Publik Di Era Digital - Fitrih, Fitrih; Majid , Abdul; Idris , Muhammad (RESPON JURNAL ILMIAH MAHASISWA ILMU KOMUNIKASI, 2022)
The objectives of this study are to describe the communication strategy of TVRI South Sulawesi in increasing its existence as a public broadcasting institution in the digital era. To find out the opportunities and challenges of TVRI South Sulawesi in improving its existence as a public broadcasting institution. The method used in this research is qualitative method. The type of research used is descriptive qualitative. There were five informants in this study. This research lasted for one month and was located at the TVRI office in South Sulawesi. Based on the results of this study, it can be concluded that the communication strategy in increasing its existence as a public broadcasting institution is to create programs that attract viewers and publish content on social media. As for the opportunities and challenges from TVRI South Sulawesi, the opportunities are wide open because TVRI has a lot of transmitters and a wide range. Meanwhile, the challenge is to change people's mindset. There are some mindsets that still think TVRI is old school television. However, TVRI will prove that this station will become a recognized part of the Indonesian television world. Trust in existing capabilities and resources.